Sustainable Development and Transhumanism – Enlightenment Visions of Future Generations - Łapiński, Jacek Leszek; Sadłocha, Łukasz (Problemy Ekorozwoju, 2021)
Both sustainable development and transhumanism are based on forecasting, meaning making judgments about what the future will be like, and they are made according to the results of scientific research. Sustainable development is an already implemented concept, yet transhumanism is still far from a similar degree of implementation. However, it is worth reflecting on their coexistence, as they already have their place in the scientific discourse. The element connecting sustainable development with transhumanism seems to be an enlightenment vision of human development. The aim of the article is to show the similarities and differences in these approaches to future generations.